SISTEM INFORMASI PENJADWALAN DAN REKOMENDASI VENDOR MENGGUNAKAN METODE ROUND ROBIN PADA MANAJEMEN FOTOINKITA - Aidil, Elqi Rahmat; Triase, Triase (IDEALIS : InDonEsiA journaL Information System, 2025)
Efficient schedule management and vendor selection are crucial aspects of the photography service industry, especially in FotoinKita’s management, which is experiencing growing demand. The previously used manual system had limitations in schedule management and vendor allocation, often leading to scheduling conflicts and customer dissatisfaction. This research employs the Round Robin method for scheduling and vendor recommendations. The method distributes tasks evenly among available vendors, ensuring a balanced workload and reducing the risk of capacity imbalances. The system is designed to integrate vendor recommendations based on the Round Robin algorithm to achieve a fair and equitable task distribution. Utilizing web-based technology, the system allows users to make bookings and schedule tasks online while receiving vendor recommendations based on specific criteria. Testing was conducted using the black-box method to ensure all features function as required. Additionally, system performance was evaluated through scheduling simulations with realistic scenarios. The implementation results showed that the system could reduce scheduling conflicts by up to 85% and increase task distribution efficiency by 90%. This system improves operational efficiency and customer satisfaction by reducing wait times and ensuring equitable task allocation. The system ensures fair task distribution among vendors and provides vendor recommendations that meet predefined criteria. The implementation of the Round Robin method in this system demonstrates that fair and efficient scheduling can be achieved, delivering significant benefits to FotoinKita’s service management.